Influence of on-site interpretation intensity on visitors to natural areas - Hughes, Michael; Morrison-Saunders, A. (Channel View Publications, 2005)
There has been some debate about the benefits of high or low intensity use of on-site media at natural areas. The former may be viewed as overkill while the latter may not achieve the intended aims. Two similar natural area sites in Australia were selected with respective high and low intensity use of on-site interpretation. Visitors at each site were surveyed immediately before and after their experience to determine site influences on site perceptions and environmental attitudes. Comparative analysis revealed the intensity of interpretation did not appear to affect perceptions or attitude influence while the character of the site experience and key visitor variables did. Site design needs to reflect interpretive media design to ensure visitor activities and subsequent effects on attitudes are consistent with conservation objectives.